Association analysis of grain zinc and iron content with agro-morphological traits in segregating population of rice - Suresh Prasad Singh; Singh, Rahul; Kumar, Anand; Kumar, Mankesh; Sinha, Sweta; Nahakpam, Sareeta; Kumar, Sunil; Shashikant; Satyendra (ORYZA-An International Journal of Rice, 2025)
The present study was carried out to investigate the associations among the agronomical and quality traits in an F2 population derived from the cross between Samba Mahsuri x Sathi. Observations were recorded on ten morphological and two grain quality (iron and zinc content) traits from each of the F2 plants. Correlation analysis revealed that grain zinc and iron content were significantly and negatively correlated with plant height, number of effective tillers per plant, number of filled grains per panicle and grain yield per plant. However, zinc and iron content in the grain recorded significantly positive correlation with each-other. Grain yield per plant showed a significant positive correlation with plant height, number of effective tillers per plant and number of filled grains per panicle.  The study concluded that while it is possible to simultaneously increase the grain iron and zinc content in the population studied, this increase is associated with a penalty on grain yield.